Evidence for Controlled Incorporation of Herpes Simplex Virus Type 1 UL26 Protease into Capsids - Sheaffer, Amy K. (American Society for Microbiology, 2000)
Herpes simplex virus type 1 (HSV-1) capsids are initially assembled with an internal protein scaffold. The scaffold proteins, encoded by overlapping in-frame UL26 and UL26.5 transcripts, are essential for formation and efficient maturation of capsids. UL26 encodes an N-terminal protease domain, and its C-terminal oligomerization and capsid protein-binding domains are identical to those of UL26.5. The UL26 protease cleaves itself, releasing minor scaffold proteins VP24 and VP21, and the more abundant UL26.5 protein, releasing the major scaffold protein VP22a. Unlike VP21 and VP22a, which are removed from capsids upon DNA packaging, we demonstrate that VP24 (containing the protease domain) is quantitatively retained. To investigate factors controlling UL26 capsid incorporation and retention, we used a mutant virus that fails to express UL26.5 (ΔICP35 virus). Purified ΔICP35 B capsids showed altered sucrose gradient sedimentation and lacked the dense scaffold core seen in micrographs of wild-type B capsids but contained capsid shell proteins in wild-type amounts. Despite C-terminal sequence identity between UL26 and UL26.5, ΔICP35 capsids lacking UL26.5 products did not contain compensatory high levels of UL26 proteins. Therefore, HSV capsids can be maintained and/or assembled on a minimal scaffold containing only wild-type levels of UL26 proteins. In contrast to UL26.5, increased expression of UL26 did not compensate for the ΔICP35 growth defect. While indirect, these findings are consistent with the view that UL26 products are restricted from occupying abundant UL26.5 binding sites within the capsid and that this restriction is not controlled by the level of UL26 protein expression. Additionally, ΔICP35 capsids contained an altered complement of DNA cleavage and packaging proteins, suggesting a previously unrecognized role for the scaffold in this process.